The Eastern borders of the EU : some contradictions and consequences : remarks about comparison between two different case-studies : the Finno-Russian border in Karelia and the Lithuanian-Byelorussian border. - A. Vitale (Wydawnictwo Instytut Slaski, 2009)
The European Union’s eastern border created a new divide in Europe, related to many problems, contradictions and consequences. The removal of internal borders within the EU and the opening of a common market were accompanied by a continuous strengthening and an increasing importance of external borders; the enlargement produced automatically a renewed cleavage between the two “Europes”. The enlargement rooted the European Union’s eastern border deep into the territory of the former Soviet Union, in the Baltic region, and reached States that are still in the process of institution-building. This paper aims to look at some contradictions and difficulties of this new EU’s border in managing security, external relations between inside and outside of the Union. As the new external border of the EU is becoming increasingly more scrutinized, it contributes to the disruption of long-standing economic and social relationships in the border regions, and ultimately a new dividing line between the “ins” and “outs” of the integration process. It adds to the complexity of the EU, changes its profile, and reaches new neighbours. It divides Europe in two parts, with the “other” Europe being either anxious to get in, or feeling excluded. The EU’s eastern border is also a contributor to the identity definition of those on both sides of the border, but the new border is also perceived as the source of some of the main security threats to the EU and non-traditional concerns emanating from Eastern and Southern Europe caused growing anxiety in the EU. The perceived security deficit has been increased the impermeability of the EU’s external border. As a result, this external border has been further strengthened and even militarized since 2004, but the restrictive border policy may at the same time undermine the headline goal of European foreign policy: the continent-wide stability. The management of these borders will have a significant impact on the stability of the rest of Europe, which finds itself outside the EU, as well as on the ...